Local generation of hydrogen for enhanced photothermal therapy - Penghe Zhao (Nature Portfolio, 2018)
The tracking and targeted release of multi-agents to cooperatively treat cancer is a developing and evolving field. Here, the authors demonstrate the anticancer effects of cubic Pd hydride nanocrystals with photoacoustic imaging properties that can release hydrogen under an NIR trigger and have photothermal effects.